2022
DOI: 10.5744/bi.2021.0021
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Femoral Neck-Shaft Angle Alterations in Post-Medieval Children with Vitamin D Deficiency Rickets

Abstract: The femoral neck-shaft angle (NSA) can adapt to the early onset of habitual but changeable loading behaviors, such as sitting, crawling, standing, and cruising behaviors, and the adoption of immature through to mature walking patterns. However, normal patterns of skeletal growth can be modified by underlying pathological conditions. Femoral head depression and neck angulation can occur during vitamin D deficiency rickets, but the pattern of NSA deformation occurring during the period of locomotor development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Modern clinical research suggests that rickets can impact the age of onset of walking (Agarwal et al, 2009). Lethargy, muscular‐skeletal pain, altered weight‐bearing due to bone softening and postural alterations associated with rickets together with contemporary childcare practices may have influenced the skeletal response to the vitamin D deficiency in a variety of ways (e.g., Hess, 1930; Ives et al, 2022) and affected the changes in cortical bone structural integrity identified here. The significant causative variables that led to the development of widespread rickets in post‐medieval urban centres are not necessarily applicable to a wide range of other population groups, although expanding research is demonstrating evidence for this metabolic bone disease from a range of past contexts (e.g., Giuffra et al, 2015; Kennedy, 1984; Littleton, 1998; Mays et al, 2018; Ortner, 2003).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Modern clinical research suggests that rickets can impact the age of onset of walking (Agarwal et al, 2009). Lethargy, muscular‐skeletal pain, altered weight‐bearing due to bone softening and postural alterations associated with rickets together with contemporary childcare practices may have influenced the skeletal response to the vitamin D deficiency in a variety of ways (e.g., Hess, 1930; Ives et al, 2022) and affected the changes in cortical bone structural integrity identified here. The significant causative variables that led to the development of widespread rickets in post‐medieval urban centres are not necessarily applicable to a wide range of other population groups, although expanding research is demonstrating evidence for this metabolic bone disease from a range of past contexts (e.g., Giuffra et al, 2015; Kennedy, 1984; Littleton, 1998; Mays et al, 2018; Ortner, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…This can potentially complicate paleopathological interpretations. Rickets was noted in historical reports as a significant factor affecting child health (see Ives et al, 2022) but it is possible that during the post‐medieval period not all children in urban London were equally susceptible to the risk of vitamin D deficiency, or equally affected by the development of skeletal changes representing the deficiency (Ives, 2018; Ives et al, 2022). Therefore, we cannot be certain that children without any skeletal changes of rickets did not have some underlying form of the deficiency.…”
Section: Methodsmentioning
confidence: 99%